Visual Literacy Design of Kebo Kicak Interactive Game for Early Age Children - Kinanti Erste Panggayuh Putri; Akbar Warisqianto; Muhammat Fansya Ubaidillah (Gondang: Jurnal Seni dan Budaya, 2025)
The decline in children’s exposure to local folktales is closely linked to the lack of digital literacy media that transform oral traditions into formats suited for digital-native learners. Kebo Kicak, a well-known folktale from Jombang Regency, holds strong cultural value and requires revitalization through accessible digital storytelling. This study aims to develop an interactive digital literacy medium in the form of an illustrated and narrated audiobook designed for kindergarten-aged children. A qualitative case study approach was applied using the Design Thinking framework, consisting of the stages of empathy, define, ideation, prototype, and user testing. Data were collected through field observations, interviews with cultural and early childhood education experts, and usability trials in local kindergartens. The prototyping process produced two audiobook modes: a self-reading mode supported by child-friendly digital illustrations, and a read-to-me mode integrating voice-over narration with gamelan-inspired background music to reinforce cultural identity. User evaluation through the User Experience Questionnaire (UEQ) indicated strong appeal, clarity, engagement, and perceived novelty. Children demonstrated positive attention, enjoyment, and improved motivation to read or listen independently, while teachers affirmed the media’s relevance for early literacy learning.The implementation of this digital storytelling medium shows that the Kebo Kicak audiobook effectively connects traditional folklore with contemporary multimedia practices. It enhances early literacy experiences while serving as a practical strategy for cultural revitalization among the digital-native generation.